Al-Nuzum al-idariyah wa-al-maliyah fi 'ahdi al-khalifah 'Umar ibn al-Khattab radi Allahu 'anhu - Sarina Bt Jamaluddin (Kolej Universiti Islam Malaysia, 2022)
This academic project discusses about the financial and management systems during the period of Caliph Umar R.A. It also reveals his contribution towards the development of financial and management systems according to the shariah. The methodologies applies in this research are library research because its relevance in getting the facts and knowledge in relation to the study. This particular Caliph had been successful in setting up Islamic financial and management systems that are in line with the Shariah Laws. In this research it is revealed that the Islamic financial and management system that were engineered and pioneered by Caliph was based on Islamic systems of finance and management is until today applicable as a reference.